Persistence of an intact HIV reservoir in phenotypically naive T cells - Venanzi Rullo, Emmanuele; Pinzone, Marilia Rita; Cannon, LaMont; Weissman, Sam; Ceccarelli, Manuela; Zurakowski, Ryan; Nunnari, Giuseppe; O’Doherty, Una (JCI insight, 2020)
Despite the efficacy of antiretroviral therapy (ART), HIV persists in a latent form and remains a hurdle to eradication. CD4+ T lymphocytes harbor the majority of the HIV reservoir, but the role of individual subsets remains unclear. CD4+ T cells were sorted into central, transitional, effector memory, and naive T cells. We measured HIV DNA and performed proviral sequencing of more than 1900 proviruses in 2 subjects at 2 and 9 years after ART initiation to estimate the contribution of each subset to the reservoir. Although our study was limited to 2 subjects, we obtained comparable findings with publicly available sequences. While the HIV integration levels were lower in naive compared with memory T cells, naive cells were a major contributor to the intact proviral reservoir. Notably, proviral sequences isolated from naive cells appeared to be unique, while those retrieved from effector memory cells were mainly clonal. The number of clones increased as cells differentiated from a naive to an effector memory phenotype, suggesting naive cells repopulate the effector memory reservoir as previously shown for central memory cells. Naive T cells contribute substantially to the intact HIV reservoir and represent a significant hurdle for HIV eradication.